Geometrical and numerical strategies in students' functional reasoning - Ponte, João Pedro da (2011)
This paper reports results of a reaserch project on the reasoning processes used by students in handling numerical functions and interpreting Cartesian graphs. Functions are a central topic in the high school and college undergraduate mathematics curriculum. Many properties of numerical functions are naturally described by their graphs, thus making particularly relevant the dialetic between numerical and geometrical aspects. In this paper, functional reasoning refers to the mental processes associated with the classical notions of functional dependence -- that is, with the notion that in some circumstances the value assumed by a certain variable depends in a weel-defined way on the value taken by another variable.